2010
DOI: 10.1021/ja107132j
|View full text |Cite
|
Sign up to set email alerts
|

Water-Soluble Organo−Silica Hybrid Nanotubes Templated by Cylindrical Polymer Brushes

Abstract: We report the preparation of water-soluble organo-silica hybrid nanotubes templated by core-shell-corona structured triblock terpolymer cylindrical polymer brushes (CPBs). The CPBs consist of a polymethacrylate backbone, a poly(tert-butyl acrylate) (PtBA) core, a poly(3-(trimethoxysilyl)propyl acrylate) (PAPTS) shell, and a poly(oligo(ethylene glycol) methacrylate) (POEGMA) corona. They were prepared via the "grafting from" strategy by the combination of two living/controlled polymerization techniques: anionic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
96
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(96 citation statements)
references
References 46 publications
0
96
0
Order By: Relevance
“…The methods for shape control of silica NPs are mainly using templates [45, 46, 51, 52] or through polymer adsorption [49]. For example, silica nanotubes can be prepared with various templates, including anodic aluminum oxide membranes [46, 47], cylindrical polymer brushes [48], and nickel-hydrazine complex nanorods [50]. Recently, Kuijk et al reported the polyvinylpyrrolidone-mediated synthesis of monodisperse silica nanorods with tunable aspect ratio in an emulsion system (Fig.…”
Section: Synthesis and Control Of The Properties Of Silica Npsmentioning
confidence: 99%
“…The methods for shape control of silica NPs are mainly using templates [45, 46, 51, 52] or through polymer adsorption [49]. For example, silica nanotubes can be prepared with various templates, including anodic aluminum oxide membranes [46, 47], cylindrical polymer brushes [48], and nickel-hydrazine complex nanorods [50]. Recently, Kuijk et al reported the polyvinylpyrrolidone-mediated synthesis of monodisperse silica nanorods with tunable aspect ratio in an emulsion system (Fig.…”
Section: Synthesis and Control Of The Properties Of Silica Npsmentioning
confidence: 99%
“…Recently, polymer brush, defined as a one-dimensional brush possessing densely grafted side chains on a linear polymer main chain or solid surfaces, has attracted much more attention due to their unique properties and several potential applications [1,2], such as high aspect ratio nanowires [3], supersoft elastomers [4], nanotubes and hollowed nanoparticles [5][6][7], photonic crystals [8][9][10], molecular tensile machines [11,12], and nanoporous materials [13,14]. Polymer brush has also been used in the liquid crystal display application for realizing the controllable alignment of liquid crystalline molecules in the devices.…”
Section: Introductionmentioning
confidence: 99%
“…For purposes of envisioning a most ideal case (e.g., a negative resist), the resist film and its synthetic chemistry would need to be much less random to allow the positioning of key functionalities in the film to become much more deterministic. [10][11][12] Figure 2 illustrates a conceptual design of a block bottle brush polymer, formed by sequential addition first with macromonomers with one set of functional groups for substrate alignment, followed by addition of different macromonomers of a second type of functional group to supply the needed lithographic crosslinking and development control properties. 1.…”
Section: Introductionmentioning
confidence: 99%